Answer:
![x {}^(3) ( {x}^(2) - 5) = - 4x](https://img.qammunity.org/2021/formulas/sat/college/iprfbb4cowzapz6lqc1x52ei0rj30tzsyd.png)
distribute x³ :
![x {}^(5) - 5 {x}^(3) = - 4x](https://img.qammunity.org/2021/formulas/sat/college/e9mbbce0ar49cl8a6748p5nhea2wk7a23n.png)
move variable to the left-hand side:
![{x}^(5) - 5 {x}^(3) + 4x = 0](https://img.qammunity.org/2021/formulas/sat/college/wifaazmyfylwm9qhaek01dpmtk75ursh1l.png)
factorize out x :
![x( {x}^(4) - 5 {x}^(2) + 4) = 0](https://img.qammunity.org/2021/formulas/sat/college/mmllehn959i3z83zoskis1vddisqf2c3m5.png)
write -5x as difference:
![x( {x}^(4) - {x}^(2) - 4 {x}^(2) + 4) = 0](https://img.qammunity.org/2021/formulas/sat/college/v0bzsk847tr4e09sqn5bi8kx4af6zfir2q.png)
factorize x² from the equation:
![x( {x}^(2) ( {x}^(2) - 1) - 4 {x}^(2) + 4) = 0](https://img.qammunity.org/2021/formulas/sat/college/63xs1pqkojvcrob6fe5e6rluz7h1vt0i2g.png)
factorize -4 from the equation:
![x( {x}^(2) ( {x}^(2) - 1) - 4( {x}^(2) - 1) = 0](https://img.qammunity.org/2021/formulas/sat/college/96n49m2dl0e4g1l96mi8x31y12ru4n8r1a.png)
factorize (x²-1) from the equation:
![x( {x}^(2) - 1)( {x}^(2) - 4) = 0](https://img.qammunity.org/2021/formulas/sat/college/74ffszaylxlvrq5yx6ln4ucnnleu5pj0p8.png)
products:
1) x = 0
*ignore this as your question wants x>0
2) x²-1 = 0
x² = 1
x = √1
x=1
3) x²-4 = 0
x² = 4
x = √4
x=2
thus, x=1, x=2